The diabetes drug semaglutide reduces infarct size, inflammation, and apoptosis, and normalizes neurogenesis in a rat model of stroke. (1st November 2019) - Yang, Xiaoyan; Feng, Peng; Zhang, Xiangjian; Li, Dongfang; Wang, Ruifang; Ji, Chenhui; Li, Guanglai; Hölscher, Christian
Abstract: Stroke is a condition with few medical treatments available. Semaglutide, a novel Glucagon-like peptide-1 (GLP-1) analogue, has been brought to the market as a treatment for diabetes. We tested the protective effects of semaglutide against middle cerebral artery occlusion injury in rats. Animals were treated with 10 nmol/kg bw ip. starting 2 h after surgery and every second day for either 1, 7, 14 or 21 days. Semaglutide-treated animals showed significantly reduced scores of neurological impairments in several motor and grip strength tasks. The cerebral infarction size was also reduced, and the loss of neurons in the hippocampal areas CA1, CA3 and the dentate gyrus was much reduced. Chronic inflammation as seen in levels of activated microglia and in the activity of the p38 MAPK – MKK – c-Jun- NF-κB p65 inflammation signaling pathway was reduced. In addition, improved growth factor signaling as shown in levels of activated ERK1 and IRS-1, and a reduction in the apoptosis signaling pathway C-raf, ERK2, Bcl-2/BAX and Caspase-3 was observed. Neurogenesis had also been normalized by the drug treatment as seen in increased neurogenesis (DCX-positive cells) in the dentate gyrus and a normalization of biomarkers for neurogenesis. In conclusion, semaglutide is a promising candidate for re-purposing as a stroke treatment. Highlights: Semaglutide is a new diabetes drug on the market. Semaglutide has neuroprotective properties in a stroke animal model. Motor activity was improved and infarct volume reduced by the drug. Loss of neurons and inflammation was reduced. Neurogenesis and growth factor cell signaling was normalized.